Miss. Code Ann. ch. 29, § 1026 (1892) - (:unkn) unknown (My University, 1892)
§ 1026: "Any person who carries concealed, in whole or in part any bowie-knife, dirk-knife, butcher-knife, pistol, brass or metallic knuckles, slung-shot, sword, or other deadly weapon of like kind or description?"
Keywords: CARRY - CONCEALED